Networks - Allara, Pamela; Alloway, Lawrence; Larsen, Lars Bang, 1972- (Cambridge, MA : The MIT Press, 2014)
Joseph, Beuys; Ursula Biemann; Roberto Chabet; Colectivo Situaciones; Critical Art Ensemble; Marcel duchamp; Peter Fend. Gego; Hans Haacke; Koncern°; Allan Kaprow; Les Levine; Pia Lindman; Mark Lombardi; Marta Minujin; Aleksandra Mir; Tanja Ostijic; Lea Porsager; Artuas Raila; Pit Schulz; Hito Steyerl; Suzanne Treister; Wolf Vostell; Stephen Willats
Connectivity before and beyond the Net -- The network as a mode of being -- Exchange is the oxygen of capital -- Corruption, intrigue, and covert solidarity.
Formerly CIP.
boek
Keywords: Internet -- Social aspects; System analysis -- Philosophy; Social networks -- Philosophy; Mass media and social integration; Art criticism